CATALYTIC ALKYLATION OF C2-C4 HYDROCARBONS - Utelbayev, Bolysbek; Aigerim, Tasmagambetova; Raila, Toktasyn; Yergali, Markayev; Maxat, Myrzakhanov (European Scientific Journal, ESJ, 2015)
The aim of this paper is development putting metals on pillar structured clay for catalytic alkylation of light hydrocarbons. The pillar structured bentonite obtained with modifying polyhydrocomplex of chromium (III) chloride. Pillar structured bentonite was used for preparation 0.5-1.0% Ru/Carrier (modifying bentonite) support catalysts where is realized alkylation of C2-C4 hydrocarbons. Process of alkylation is carried out at partial pressure of hydrogen 0.5-1.0MPa. The outcome of high octane number components 2.2.4 three-methylpentane and 2.2.3 three-methylpentane achieved about 40%. At alkylation butane-butene mixture yield of isooctane achieved 60%.